First report of pseudohermaphroditism in cephalopods - Ortiz, Nicolás (2006)
Several malformations have been reported for cephalopods, involving a variety of internal and external structures. However, so far there are no published records of pseudohermaphroditism for the class. During a study of the reproductive biology of the red octopus, Enteroctopus megalocyathus (Gould 1852) in Golfo Nuevo, Patagonia, Argentina, we caught a specimen with a complete female reproductive system, with a normal terminal organ and an incomplete male spermatophoric complex. Histological comparisons with normal males and females did not reveal any testicular tissue in the ovary, so we suggest that this individual may represent the first case of pseudohermaphroditism in a cephalopods. When considering the potential causes of this abnormality, the influence of endocrine disruptors with an exogen origin should not be discarded. For instance, tributyltin contamination, as recorded previously in the gulf, and its relation to imposex in gasteropods should not be underestimated. Aditionally, this animal confirm that in immature octopus normal development of male ducts and glands is possible in the absence of testicular tissue.